Productive learning – interpretations - Bárdossy, Ildikó (Autonomy and Responsibility Journal of Educational Sciences, 2022)
The present study aims at outlining a framework of interpretetion and altering approaches of productivity and productive learning based on selected sources and developmental experiences. The author on one hand intends to illustrate the deep roots of productive learning and on the other hand she points out its actuality in recent public education, higher education, and in diverse institutions (those may be interpreted as intelligent learning organisations). As a consummation of a demand, a promise, a possibility, a critical approach productive learning is as actual as it used to be when it began.